Alpha-Glucosidase inhibitory activity in hexane extracts of some plants from kurdistan province - MS Poursharifi; MA Zarei (Institue of Medicinal Plants, ACECR, 2016)
Background: Diabetes mellitus is a most serious and chronic disease that is characterized by high blood glucose levels, especially after feeding, namely postprandial hyperglycemia. Alpha-glucosidase, as a carbohydratase catalyses the liberation of alpha-glucose from the nonreducing end of some carbohydrates from foods in digestive tract. Consequently, retard absorption of glucose by the inhibition of carbohydrate hydrolyzing enzymes is one of the therapeutic approaches to decrease the postprandial hyperglycemia. Commercial ;alpha-glucosidase inhibitors have been used to treat diabetes, but they exhibit some serious side effects, including liver disorders, flatulence, and abdominal pain. Recently, a great deal of attention has been paid to natural products like plants,as a reliable source forbioactive compounds. Those compounds may act as powerful inhibitors of alpha-glucosidase. Objective: The aim of this study was to find new potent inhibitors for Alpha-glucosidase among plant extracts. Methods: Hexan extracts of 60 plants species were screened for their Alpha-glucosidase inhibitory activity at 0.001, 0.01, 0.1 and 1 mg/mL concentration. Acarbose, dissolved in buffer, was used as a positive control. Every experiment was done in triplicate. Results: Descurania Sophia (L.) Webb & Berth, Fumaria vailantii Loisel, Ferula Haussknechti Wolf ex Rech,Haplophyllum acutifolium (DC.)G.Don, Isatis cappadociaca Desv., Eremostachys laevigata Bunge, Silene aucheriana Boiss exhibited more than 60% alpha-glucosidase inhibitory activity. Among them, Descurania Sophia, Fumaria vailantii and Ferula haussknechti exhibited significant alpha glucosidase inhibitory activity with IC50 values of 0.9 µg/ml, 24.55 µg/ml and 2.71 µg/ml, respectively. Conclusion: Because of its high inhibitory activity and low IC50, Descurania Sophia extract would be interesting for further studies.